Cerebellar and subcortical contributions to working memory manipulation - Joshua B. Tan; Isabella F. Orlando; Christopher Whyte; Annie G. Bryant; Brandon R. Munn; Giulia Baracchini; Maedbh King; Claire O’Callaghan; Eli J. Müller; James M. Shine (Communications Biology)
Abstract Working memory is critical for manipulating and temporarily storing information during cognitive tasks such as problem-solving. Most models focus primarily on cortical-cortical interactions, neglecting subcortical and cerebellar contributions. Given the extensive connectivity between the cerebellum, subcortex, and cortex, we hypothesize that they contribute distinct, yet complementary, functions during working memory manipulation. To test this, we used functional Magnetic Resonance Imaging (fMRI) to measure blood oxygen-level dependent (BOLD) activity while participants performed a mental rotation task. Our results revealed a distributed network spanning the cortex, subcortex, and cerebellum that differentiates rotated from non-rotated stimuli and correct from incorrect responses. Notably, delayed responses in premotor, subcortical, and cerebellar regions during incorrect trials, suggest that their precise recruitment is crucial for successful working memory manipulation. These findings expand current models of working memory manipulation, revealing the collaborative role of subcortical and cerebellar regions in coordinating higher cognitive functions.